Evaluation of Udaipur Rock Phosphate as Phosphorus Fertilizer in Soybean (Glycine max L. Merrill) Grown on Acid Upland Soils of Nagaland - Engrala Ao; R.C. Gupta, I. Jaleel Basha, A. K. Singh (Journal of the Indian Society of Soil Science, 2018)
Phosphorus (P) is one of the limiting nutrients in most of the soils due to its low solubility and high fixation. Low-grade Udaipur rock phosphate (URP) was evaluated as source of P to soybean (Glycine max L. Merrill). The study revealed that Bray’s P increased significantly over 15 days of incubation, and the increase was observed up to 90 days. No definite change was observed in the pH of soil. The lowest pH was recorded with phosphate solubilizing microorganism (PSM) followed by partially acidulated URP (PAURP) + FYM. In the field experiment, the yield and yield attributes of soybean showed significant response to different treatments. Likewise, P uptake and P use efficiency (PUE) were highest under PAURP + FYM. The organic carbon content was not significantly affected by P sources with or without FYM and PSM. However, the treatment effect was significant for available N, P and K, with highest under PAURP + FYM. It can be concluded that the application of PAURP @ 60 kg P2O5 along with FYM @ 5 t ha-1 is most effective to increase the yield and quality of soybean and residual soil nutrient status under acidic soil condition of Nagaland. Also, the application of PAURP is a better alternative to the conventional Pfertilizers to minimize the cost.